89 Radiofrequency Ablation of the Interventricular Septum to Treat Left Ventricular Outflow Tract Gradients in HOCM: Novel Use of Cartosound Technology to Guide Ablation. (6th June 2015) - Cooper, Robert; Modi, Simon; Shahzad, Adeel; Hasleton, Jonathan; DiGiovanni, Joseph; Hall, Mark; Todd, Derick; Stables, Rodney
Abstract : Introduction: Septal reduction is required for HOCM patients with severe LVOT gradients and symptoms refractory to medications. Myectomy cannot be performed in all due to operative risk and patient choice. Alcohol ablation cannot be performed in 5–15% due to technical difficulties and reliance on septal coronary anatomy. A method of delivering percutaneous damage to the basal septum that is not reliant on coronary anatomy is desirable. Methods: 5 patients underwent RF ablation; we describe follow up at 6 months in 4. CARTOsound technology (Intracardiac echocardiography (ICE) merged with the electroanatomic mapping system, CARTO) was used to create a virtual shell of the LV and aorta (Figure 1 (F1), panel A). The precise SAM-septal contact area is ascertained from realtime ICE images and is superimposed onto the CARTO LV shell (pink area, F1, B). This pink area becomes the target for RF energy delivery. Left bundle branch conduction tissue is mapped and superimposed (F1, C). Intravenous heparin is given to keep activated clotting time >250 s. A mean of 31.7 (28–36) minutes of RF energy (50W, 60º) was delivered to the target area using retrograde aortic access and an irrigated 4 mm SmartTouch D-curve ablation catheter (F1, D) Results: Peak resting gradient improved from 64.25 (±50.60) to 12.25 (±2.50) mmHg. Valsalva/exercise gradient improved from 93.50 (±30.88) to 23.25 (±8.30) mmHg. SAM improved in all patients. IVSd reduced from 18.25 (±1.89)mm to 16.75 (±2.5)mm. All patients improved NYHA class from 3 to 2. CPEX data was available in 3. Pre-procedural peak VO2 measured 15.48 (±2.27) mL/min/Kg, this improved to 16.53 (±5.16). Total exercise time increased from 558 (±129) to 730 (±63)secs. EQ5D-5L quality of life index value increased from 0.57 (±0.17) to 0.65 (±0.18). Health score improved from 44 (±18.93) to 70 (±3.54). Two patients had CMR post ASA. Scar can be seen upto 8 mm depth at the endocardial surface of the LV target myocardium (Figure 2 ). Scar measured 6.3 and 2.2 g respectively, representing 2.4 and 1.1% of total LV mass. LV mass prior to ablation measured 259 and 198 g. This reduced to 236 and 160 g, representing a 9 and 19% reduction. Patient 4 died following femoral artery access point bleeding complications. Hypotension was poorly tolerated leading to cardiac arrest. The artery was repaired surgically but deterioration over the subsequent 48 h lead to multi-organ failure. Patient 5 had a paradoxical increase in LVOT gradients post procedure requiring unplanned ITU care. Conclusions: Radiofrequency ablation to treat LVOT gradients in HOCM using CARTOsound shows significant promise. The unprecedented accuracy of damage reduces SAM and results in improvements in LVOT gradients, symptoms and quality of life in this preliminary group. A small amount of damage at the correct location can lead to significant LV mass regression. This indicates part of the hypertrophy in HCM is afterload dependent